TEACHERS’ ACADEMIC QUALIFICATIONS AND THEIR LEVELS OF PROFICIENCY ON THE ESSENTIAL TEACHING SKILLS: A SURVEY STUDY AMONG TEACHERS OF EARLY CHILDHOOD EDUCATION PROGRAMS - Sindy Anugerah Wati (Widya Mandala Surabaya Catholic University, 2023)
This paper reports on a study which aims at describing the levels of teaching proficiency among the ECCE (Early Childhood Center Education) teachers based on their essential teaching skills in preparing lesson plans, carrying out teaching and learning activities, and assessing learning. This study involved ECCE teachers having a linear educational background (i.e., a bachelor’s degree in early childhood education) and those having a non-linear educational background (i.e., a non a bachelor’s degree in early childhood education). This study is descriptive quantitative in nature employing a survey design. There were 170 ECCE teachers in Sawahan, Nganjuk, East Java participated in this study. Of these participants, 120 had a linear educational background and 50 had a non-linear educational background. The research data were collected using a questionnaire with 30 questions. The results of the study showed that among the teachers involved in the study, 85.88% could be said to be very proficient, 2.94% could be said to be proficient, 8.82% teachers could be said to be less proficient and 2.36% of the teachers could be said to be not proficient. There is no difference in the levels of teaching proficiency between teachers who have linear and non-linear educational background because teachers who do not have linear educational background have got competency enrichment opportunities through teacher trainings, seminars, sharing knowledges with colleagues, and practices in ECCE teacher organizations